Evaluation of Carcass Production of PO Cattle Based on Heart Girth Measurement, Body Condition Score and Slaughter Weight - Haryoko, I; Suparman, P (ANIMAL PRODUCTION, 2009)
The objective of study was to evaluate of carcass production of PO beef cattle based on measurement of heart girth, body condition score (BCS), and slaughter weight.  It was conducted in the slaughtering house at Mersi Purwokerto city.  The materials for this study were 60 heads of male PO breed cattle.  Simple random sampling was used for taking samples.  Data was analyzed by using multiple regression equation to determine the effects of heart girth, BCS, and slaughter weight on carcass weight.  The potency of carcass relative growth was assessed with Huxley allometric equation. The result showed that heart girth did not differ significantly (P>0.05), BCS had significant effect (P<0.01) on carcass weight and percentage, and slaughter weight had significant effect (P<0.01) on carcass weight.  Relative growth of carcass weight to slaughter weight had a high potential (b=1.136), otherwise relative growth of carcass proportion to slaughter weight had a less potential (b=0.136).  It could be concluded that (1) carcass weight could be predicted using BCS and slaughter weight parameters, and (2) PO beef cattle slaughtered had a good of relative growth potential for the carcass. (Animal Production 11(1): 28-33 (2009) Key Words: PO beef cattle, heart girth, BCS, slaughter weight, carcass